Head Nurse Supervision as an Effective Strategy to Improve Nursing Retention and Performance - Desma Elvita; Cicilia Ika Wulandari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Suboptimal supervision by ward heads has been identified as a contributing factor to low retention and high turnover among hospital nurses. Strengthening supervisory practices is therefore essential to enhance performance, job satisfaction, and workforce stability within nursing services. This study aims to analyze the influence of ward head supervision on job satisfaction and organizational commitment among hospital nursing staff. This systematic literature review employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework and the PICOT strategy. Literature searches were conducted through Google Scholar, PubMed, ScienceDirect, ProQuest, and Gale using keywords related to ward head supervision, job satisfaction, organizational commitment, and hospital settings. The review followed a rigorous and structured process, including critical appraisal using the Critical Appraisal Skills Programme (CASP) to assess methodological quality. From the 15 articles reviewed, most studies demonstrated that ward head supervision and leadership exert a positive influence on nurse performance, quality of work life, job satisfaction, and organizational commitment. Structured, supportive, and development‑oriented supervision was shown to reduce burnout, improve compliance with standard operating procedures, and strengthen nurse retention. However, the effectiveness of supervision is highly dependent on the quality, consistency, and contextual appropriateness of its implementation. In conclusion, ward head supervision and leadership play a pivotal role in improving nurse performance, adherence to standard operating procedures, and patient safety. Supportive and well‑structured supervisory practices, combined with effective leadership, contribute significantly to service quality and the overall well‑being of nurses in hospital settings.Keywords: Ward head supervision; Nurse job satisfaction; Nursing service quality.